2019
DOI: 10.1103/physreve.99.033205
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Compton scattering of an ultraintense laser pulse in a plasma

Abstract: Laser pulses traveling through a plasma can feature group velocities significantly differing from the speed of light in vacuum. This modifies the well-known Volkov states of an electron inside a strong laser-field from the vacuum case and consequently all quantum electrodynamical effects triggered by the electron. Here we present an in-depth study of the basic process of photon emission by an electron scattered from an intense short laser pulse inside a plasma, labeled nonlinear Compton scattering, based on mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 83 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…In addition, the average OAM of a single electron (>10 MeV) is up to 1.56 × 10 7 ħ and according to ICS a single photon (>0.6 MeV, calculated based on the 10 MeV electron energy) gains averaged OAM of 2.3 × 10 5 ħ , suggesting a conversion efficiency of 1.5% for OAM. While the plasma may act as a non-trivial background affecting the ICS rates 34 , we found that in our case the plasma is opaque to the laser field and the latter is dominating in the head-on collision geometry.…”
Section: Results and Analysismentioning
confidence: 57%
“…In addition, the average OAM of a single electron (>10 MeV) is up to 1.56 × 10 7 ħ and according to ICS a single photon (>0.6 MeV, calculated based on the 10 MeV electron energy) gains averaged OAM of 2.3 × 10 5 ħ , suggesting a conversion efficiency of 1.5% for OAM. While the plasma may act as a non-trivial background affecting the ICS rates 34 , we found that in our case the plasma is opaque to the laser field and the latter is dominating in the head-on collision geometry.…”
Section: Results and Analysismentioning
confidence: 57%
“…( 19), but with the k µ appearing no longer lightlike. (The same approximation is assumed in [858]. )…”
Section: Reduction Of Ordermentioning
confidence: 98%
“…Thus, looking for new (even approximate) analytic solutions to the Dirac equation in more realistic interaction configurations is necessary. Initial progress in this direction includes focusing , standing waves (King and Hu, 2016;Lv et al, 2021), rotating electric fields (Raicher et al, 2015;Raicher and Z. Hatsagortsyan, 2020) and plasma environments (Mackenroth et al, 2019b;Raicher and Eliezer, 2013).…”
Section: Theoretical Questionsmentioning
confidence: 99%